1995
DOI: 10.1115/1.2803288
|View full text |Cite
|
Sign up to set email alerts
|

A Mechanistic Approach to the Prediction of Material Removal Rates in Rotary Ultrasonic Machining

Abstract: An approach to modeling the material removal rate (MRR) during rotary ultrasonic machining (RUM) of ceramics is proposed and applied to predicting the MRR for the case of magnesia stabilized zirconia. The model, a first attempt at predicting the MRR in RUM, is based on the assumption that brittle fracture is the primary mechanism of material removal. To justify this assumption, a model parameter (which models the ratio of the fractured volume to the indented volume of a single diamond particle) is shown to be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
50
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(53 citation statements)
references
References 7 publications
2
50
0
1
Order By: Relevance
“…Desde entonces, los modelos se pueden agrupan en dos grupos: uno que se basa en un material frágil y el otro en un material dúctil (35,36). Entre ellos, hay modelos teóricos que tienen en cuenta el principio de rotura por indentación (34) mientras otros se basan en modelos mecanísticos (37). Adicionalmente, se pueden encontrar trabajos relacionados con desarrollos para recubrir las herramientas de diamante (17).…”
Section: Introductionunclassified
“…Desde entonces, los modelos se pueden agrupan en dos grupos: uno que se basa en un material frágil y el otro en un material dúctil (35,36). Entre ellos, hay modelos teóricos que tienen en cuenta el principio de rotura por indentación (34) mientras otros se basan en modelos mecanísticos (37). Adicionalmente, se pueden encontrar trabajos relacionados con desarrollos para recubrir las herramientas de diamante (17).…”
Section: Introductionunclassified
“…A theoretical material removal model in drilling advanced ceramics was established based on brittle fracture mode [6]. This model discussed the relationship between cutting parameters and material removal rate (MRR) but not predicted the drilling force model [7].…”
Section: Introductionmentioning
confidence: 99%
“…In previous study and literature review [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17], it is found that there was main focus on machining ceramics and its related composite materials. The research work on rotary ultrasonic drilling of CFRP materials is rare especially on CFRP-T700.…”
Section: Introductionmentioning
confidence: 99%
“…A better surface quality for the workpiece with less sub-surface damages (Qu et al, 2000). An increased material removal rate (Pei et al, 1995).…”
Section: Introductionmentioning
confidence: 99%